Contemporary advertising - Arens, William F (McGraw - Hill, 2006)
Contemporary Advertising, 10/e, is one of the best-selling advertising texts in this field. Known as the “coffee table book” for Advertising, it is known for its current examples, the author’s ability to pull from real-world experiences, and the clear writing style. Taking a comprehensive view of the industry, this text presents advertising from the creative stand-point and Arens draws from his own industry experience to lend life to the examples. Author Bill Arens continues to address the importance of Integrated Marketing Communications (IMC) in the field of Advertising and how it impacts advertising strategy through featured examples of IMC campaigns.